2019
DOI: 10.1038/s41396-019-0533-6
|View full text |Cite
|
Sign up to set email alerts
|

Serial horizontal transfer of vitamin-biosynthetic genes enables the establishment of new nutritional symbionts in aphids’ di-symbiotic systems

Abstract: Many insects depend on obligate mutualistic bacteria to provide essential nutrients lacking from their diet. Most aphids, whose diet consists of phloem, rely on the bacterial endosymbiont Buchnera aphidicola to supply essential amino acids and B vitamins. However, in some aphid species, provision of these nutrients is partitioned between Buchnera and a younger bacterial partner, whose identity varies across aphid lineages. Little is known about the origin and the evolutionary stability of these di-symbiotic sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 88 publications
(113 reference statements)
5
109
4
1
Order By: Relevance
“…Because of its strict vertical transmission, Buchnera has undergone long-term coevolution with its aphid hosts [5]. However, due to the metabolic losses caused by rapid genome deterioration in Buchnera [6], some aphid species of the subfamilies Lachninae, Chaitophorinae, and Aphidinae have established co-obligate associations with other symbiotic partners [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its strict vertical transmission, Buchnera has undergone long-term coevolution with its aphid hosts [5]. However, due to the metabolic losses caused by rapid genome deterioration in Buchnera [6], some aphid species of the subfamilies Lachninae, Chaitophorinae, and Aphidinae have established co-obligate associations with other symbiotic partners [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…More details are reviewed in Oliver et al [44], Zytynska and Weisser [45], and Guo et al [46]. In addition, several facultative symbionts seem to have established coobligate associations along with Buchnera in certain aphid species, such as Serratia symbiotica, Erwinia haradaeae, Fukatsuia symbiotica, Hamiltonella defensa, and Sodalis in some Lachninae species [21,[47][48][49][50][51] and Wolbachia in Pentalonia nigronervosa [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been now shown that these ancient symbionts establish a di-symbiotic relationship with newly acquired bacterial species. Manzano-Marín et al (2020) have reported that Erwinia, (which is a newly acquired symbiont of aphids) complements Buchnera (an ancient symbiont) by serial horizontal transfer of several vitamin biosynthesis genes and thus, compensating for the massive gene loss undergone by Buchnera during the long period of its association with its insect host. Similarly, a horizontal gene transfer event was observed between Cardinium and its donor organisms, Wolbachia and Rickettsia, which counterbalance the significant gene loss undergone by Cardinium to adapt to the gut environment of its host (Zeng et al, 2018).…”
Section: Implications Of Genome Size Reduction For the Endosymbiotic mentioning
confidence: 99%